Confused Robots and Incompetent Humans in Jean-Pierre Jeunet’s Bigbug (2022) - Kim, Hyunjin (Alternative francophone)

(untitled) (University of Alberta, Department of Modern Languages and Cultural Studies, 2025)
Jean-Pierre Jeunet has been working on the presentation of struggling human bodies, in his films such as Delicatessen (1991), La Cité des enfants perdus/The City of Lost Children (1995), and most recently, Bigbug (2022). In Bigbug’s fictional 2045, human beings are finally liberated from the duties of house chores. Nevertheless, they no longer have self-determination. Because of the A.I. system’s error, human characters in this film are confined in a house with house robots. This article studies the relationship between human bodies and artificial intelligence in Bigbug, through the lens of transhumanism and animality studies. By transhumanism, I mean an attempt to transform and adapt one’s body with or without technology. I argue that Jeunet’s sense of humour functions as an impetus to encourage his characters to continuously adapt and transform themselves in limited space. Moreover, the animality was discussed differently in this film: instead of comparing animals to humans, Yonyx, the A.I. androids identify humans with animals, mocking the animality of living beings. Referring to Steen Christiansen’s term "terminal films," this article examines how immobile, restricted human bodies co-exist with and resist artificial intelligence in our everyday household.